Scoring Points with Purpose: The Interplay of Passion at Work and Corporate Social Responsibility in Sports Organizations - Christos Anagnostopoulos (Journal of Applied Sports Management, 2024)
This article explores the dynamic relationship between passion at work and corporate social responsibility (CSR) within sports organizations, highlighting how CSR initiatives can actively nurture and enhance employees’ passion for their careers in this sector. Drawing on 15 years of research in this area, I reference two relevant theoretical approaches that provide a solid foundation for my arguments. Through this discussion, I advocate for a strategic alignment of employee passion and CSR, illustrating how such integration can positively influence both organizational culture and community engagement. Ultimately, this article calls for a deeper understanding of how passionate employees, empowered by meaningful CSR initiatives, can drive transformative change within the sporting landscape.
Keywords: Passion at work; CSR; Well-being; positive organizational behavior